A 'Mediterranean ice-cream': Sensory and nutritional aspects of replacing milk cream with extra virgin olive oil. (March 2023) - Tagliamonte, Silvia; De Luca, Lucia; Donato, Antonietta; Paduano, Antonello; Balivo, Andrea; Genovese, Alessandro; Romano, Raffaele; Vitaglione, Paola; Sacchi, Raffaele
Graphical abstract: Highlights: Ice-creams have been developed replacing milk cream with extra virgin olive oil (EVOO) EVOO-ice-creams showed an increased intensity of sensory descriptor "grassy" EVOO-ice-creams had less saturated and more mono- and poly-unsaturated fatty acids. EVOO-ice-creams provided bioaccessible polyphenols and increased antioxidant activity. Abstract: In this study, we explored the sensory and nutritional properties of innovative ice-creams designed totally replacing cow's milk cream with extra virgin olive oil (EVOO). Milk and chocolate flavored ice-creams containing 14.1% and 10.2% milk cream or 5.1% and 3.6% of EVOO were produced. In a triangle test, only the milk-flavored ice-cream with EVOO was distinguished from its traditional counterpart whereas in a quantitative descriptive sensory analysis EVOO ice-creams showed an increased intensity of the descriptor "grassy" that was supported by the greater concentrations of specific volatile organic compounds coming from EVOO, compared to traditional ice-creams. Moreover, EVOO ice-creams contained less saturated fatty acids and more mono- and poly- unsaturated fatty acids along an increased concentration of bioaccessible polyphenols and antioxidant activity measured after an in vitro digestion, which was more pronounced in milk-flavored sample. Data showed that EVOO can be a functional fat replacer in ice-cream recipes to produce healthier products.